Konservasi Genetik Ikan Kakap Putih (Lates calcarifer, Bloch, 1790) Melalui Pendekatan DNA Barcoding dan Analisis Filogenetik di Sungai Kumbe Merauke Papua - Dandi Saleky; Muhammad Dailami (Universitas Diponegoro, 2021)
Genetic data is very important as the basis for fisheries management and conservation related to connectivity between regions and population structure. White snapper Fish is one of the fish that has high economic value which is utilized either by its meat or by its swim bladder. This research was aimed to identify the species of white snapper fish were collected from the Kumbe River, Merauke Regency, Papua using the Cytochrome Oxidase I gene. The results shows that this sample is a species of Lates calcarifer, Bloch, 1790 with 100% similarity. The haplotype of white snapper fish from Merauke has similarities with the haplotype from Australia, Malaysia and China, this indicating that there is gene flow and connectivity among those locations. The phylogenetic tree explains the grouping of species based on genetic distance and the level of DNA Sequences similarities. Molecular approach can be used in the management and conservation of fish with high economic value.